Multimedia Center: Strategi Dinas Komunikasi Informatika Persandian dan Statistik Provinsi Kalimantan Tengah dalam Pengelolaan Informasi - Sofiya, Sofiya; Fadli, Syairil; Setiawan, Heri (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2023)
Online media has become one of the media for disseminating accurate and fastest information to the public. The multimedia center is an online medium used by the Central Kalimantan Province Information, Coding, and Statistics Communication Service to manage information for the public. This research focuses on the public relations of the Central Kalimantan Province Information, Coding, and Statistics Communication Service in using communication strategies to manage information conveyed to the public through a multimedia center. This research was conducted to find out and describe the public relations communication strategy of the Information, Coding, and Statistics Communication Service. This research aims to find out how the public relations communication strategy of the Central Kalimantan Provincial Communication Information, Coding, and Statistics Service manages information through a multimedia center using descriptive qualitative research. Descriptive research is research that tries to understand the phenomena that occur at the Central Kalimantan Province Information Communication, Encryption, and Statistics Service regarding what the research subjects feel. Using Harold D. Laswel's communication strategy theory as reinforcement for the strategy used. The data sources in this research contain primary and secondary data. Primary data was generated through face-to-face interviews with the Public Relations of the Central Kalimantan Province Information, Coding, and Statistics Communication Service and public communications management staff. Meanwhile, secondary data was obtained through the Multimedia Center website, previous research, books, journals, and websites. This research utilizes a purposive sampling strategy; the data instruments used are in-depth interviews, observation, documentation, and the validity of the data and conclusions. By implementing this strategy, the Central Kalimantan Province Information, Coding, and Statistics Communication Service found